A mutation in the Arabidopsis thaliana cell wall biosynthesis gene pectin methylesterase 3 as well as its aberrant expression cause hypersensitivity specifically to Zn. (5th August 2013) - Weber, Michael; Deinlein, Ulrich; Fischer, Sina; Rogowski, Michaela; Geimer, Stefan; Tenhaken, Raimund; Clemens, Stephan
Summary: Defects in metal homeostasis factors are often accompanied by the loss of metal tolerance. Therefore, we screened for mutants with compromised growth in the presence of excess Zn 2+ in order to identify factors involved in Zn biology in plants. Here we report the isolation of six ozs (overly Zn sensitive) ethyl methanesulfonate Arabidopsis thaliana mutants with contrasting patterns of metal sensitivity, and the molecular characterization of two mutants hypersensitive specifically to Zn 2+ . Mutant ozs1 represents a non‐functional allele of the vacuolar Zn transporter AtMTP1, providing additional genetic evidence for its major role in Zn 2+ tolerance in seedlings. Mutant ozs2 carries a semi‐dominant mutation in the gene encoding pectin methylesterase 3 ( AtPME3 ), an enzyme catalyzing demethylesterification of pectin. The mutation results in impaired proteolytic processing of AtPME3. Ectopic expression of AtPME3 causes strong Zn 2+ hypersensitivity that is tightly correlated with transcript abundance. Together these observations suggest detrimental effects on Golgi‐localized processes. The ozs2 but not the ozs1 phenotype can be suppressed by extra Ca 2+, indicating changes in apoplastic cation‐binding capacity. However, we did not detect any changes in bulk metal‐binding capacity, overall pectin methylesterification status or cell wall ultrastructure in ozs2, leading us to hypothesize that the ozs2 mutation causes hypersensitivity towards the specific interference of Zn ions with cell wall‐controlled growth processes.